Budidaya Terpadu Ikan dan Sayuran melalui Metode Akuaponik Di Desa Serut Kecamatan Panti Kabupaten Jember - Parawita Dewanti (Warta Pengabdian, 2019)
Abstract Socialization and hydroponic business practices have been carried out through a Posdaya established by the Jember University Service Institute in Karang Anom Hamlet in Serut village, Panti District, Jember Regency. Serut village was chosen as a target in the partner village development program because it has high potential for the development of hydroponic vegetables in terms of location, community awareness and independence and has an entrepreneurial spirit. On the other hand, the results of observations also found that some residents in Karang Anom Hamlet in Serut Village, Panti District have a fish farming business that has been running for the past few years. Efforts of integrated cultivation of vegetables and fish through the Aquaponics method are expected to produce 2 products at once in a one-time production process, so that products that will benefit the local community and the community at large to meet family food and nutrition are expected. and skills in managing integrated fish and vegetable cultivation in one production process. Therefore, adequate facilities and infrastructure are needed so that the partner groups can utilize aquaponics technology. The results of the activity showed that there was a positive response from the members of the partner group which was shown by the enthusiasm of the participants in participating in a series of training from start to finish. The product has been obtained in one aquaponic production per month will produce 50 kg of catfish and 40 kg of vegetables. For 3 units of fish ponds, 150 kg of catfish and 120 kg of vegetables will be produced within 3 months. Keywords: Aquaponics, Catfish, Vegetables, Hydroponics